Improving public stigma, sociocultural beliefs, and social identity for people with epilepsy in the Aseer region of Saudi Arabia - Nawal F. Abdel Ghaffar; Reem N. Asiri; Laith N. AL-Eitan; Reem S. Alamri; Reem M. Alshyarba; Faris A. Alrefeidi; Ashwag Asiri; Mansour A. Alghamdi (Epilepsy & Behavior Reports, 2021)
Differences in the sociocultural practice and biases against people with epilepsy (PWE) largely contribute to the development of stigmatization. In this study, we evaluated factors that impact stigma for PWE involved in evolution and maintenance to report changes in the public awareness and cultural practices. We performed a cross-sectional study in which data were collected from a self-administered electronic survey composed of 33 items targeting the population in the Aseer region. Feedback response was obtained from 937 respondents. Of these, 921 participants (98.3%) had heard or read about the disorder previously. Approximately 84.8% believed that epilepsy was one of the brain disorders. 95.8% disagreed that epilepsy was due to a contagious disease. However, 40.1% of the responders were convinced that it was the result of a spiritual reason. Still, more than 9% believed treating PWE should be approached spiritually. About 75% felt that epilepsy could be the results of a test delievered by God. In addition to the clinical impact from seizures in PWE, it carries a social label and public stigma that influences one's social prognosis. Raising awareness through campaigns would improve the knowledge and practices of the population and hence provide a healthier environment for PWE, alleviating feelings of stigma, and improving their quality of life.